An Inflammatory Pseudotumor Arising from Pterygopalatine Fossa with Invasion to the Maxillary Sinus and Orbital Cavity. (18th June 2015) - Yokoi, Hidenori; Yazawa, Takuya; Matsumoto, Yuma; Ikeda, Tetsuya; Fujiwara, Masachika; Ohkura, Yasuo; Kohno, Naoyuki
Abstract : We report a patient who had an inflammatory pseudotumor (IPT) that invaded to the maxillary sinus and orbital cavity, with the left pterygopalatine fossa as the principal site; this is a very rare case. The patient was an 83-year-old woman who suddenly became aware of impairment in the eyesight and visual field of the left eye. CT images showed a neoplastic lesion that invaded to the maxillary sinus and orbital cavity, with the left pterygopalatine fossa as the principal site, and also showed contrast effects. To obtain a definitive diagnosis from histopathological analysis, the lesion was biopsied, and she was diagnosed as the inflammatory pseudotumor with the immunohistochemical study and multiplex polymerase chain reaction-based clonality assays. The patient had a lymphoid-predominant lesion that responded to radiotherapy but corticosteroids were not effective. It is important to scrutinize the pathology to avoid unnecessary and mutilating surgery.